Gene Editing with Helper-Dependent Adenovirus Can Efficiently Introduce Multiple Changes Simultaneously over a Large Genomic Region - Palmer, Donna J. (Mol Ther Nucleic Acids, 2017)
Helper-dependent adenoviral vectors (HDAds) possess long homology arms that mediate high-efficiency gene editing. These long homology arms may permit simultaneous introduction of multiple modifications into a large genomic region or may permit a single HDAd to correct many different individual mutations spread widely across a gene. We investigated this important potential using an HDAd bearing 13 genetic markers in the region of homology to the target CFTR locus in human iPSCs and found that all markers can be simultaneously introduced into the target locus, with the two farthest markers being 22.2 kb apart. We found that genetic markers closer to the HDAd’s selectable marker are more efficiency introduced into the target locus; a marker located 208 bp from the selectable marker was introduced with 100% efficiency. However, even markers 11 kb from the selectable marker were introduced at a relatively high frequency of 21.7%. Our study also revealed extensive heteroduplex DNA formation of up to 10 kb with no bias toward vector or chromosomal repair. However, mismatches escape repair at a frequency of up to 15%, leading to a genetically mixed colony and emphasizing the need for caution, especially if the donor and target sequences are not 100% homologous.